Do trade deals encourage environmental cooperation? - Jean-Frédéric Morin; Vera Chaudhuri; Mathilde Gauquelin (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
Trade agreements have mixed effects on the environment. On the one hand, trade generates additional pollution by raising production levels. Trade rules can also restrict the capacity of governments to adopt environmental regulations. On the other hand, trade agreements can favour the diffusion of green technologies, make production more efficient and foster environmental cooperation. Whether the overall effect is positive or negative partly depends on the content of the trade agreement itself. Recent studies have found that trade agreements with detailed environmental provisions, in contrast to agreements without such provisions, are associated with reduced levels of CO2 emission and suspended particulate matter (Baghdadi et al., 2013; Zhou, 2017). It remains unclear, however, which specific provisions have a positive environmental impact and how they are actually implemented. This briefing paper discusses how provisions on environmental cooperation in trade agreements can contribute to better environmental outcomes. It is frequently assumed that the more enforceable environmental commitments are, the more likely governments are to take action to protect the environment (Jinnah & Lindsay, 2016). This assumption leads several experts to argue in favour of strong sanction-based mechanisms of dispute settlement in order to ensure the implementation of trade agreements' environmental provisions. Nevertheless, there is evidence to suggest that softer provisions can result in increased environmental cooperation, which can in turn favour domestic environmental protection (Yoo & Kim, 2016; Bastiaens & Postnikov, 2017). The European Union privileges this more cooperative approach in its trade agreements, and a recent European non-paper (2018) stresses that a sanction-based approach is a disincentive for ambitious environmental commitments and can result in a political backlash. To shed light on this debate, this paper examines the design and the implementation of cooperative environmental provisions of trade agreements. Our analysis is based on three main data sources. First, we make use of the TRade & ENvironment Dataset (TREND) which provides information on 285 types of environmental provisions included in 688 trade agreements signed since 1947 (Morin et al., 2018; see also www.TRENDanalytics.info for an online visualisation tool for the data). Second, we draw on official documents to better understand how these provisions are implemented domestically. Third, we fill the gaps using information provided by 12 interviewees who work for 7 different governments. This briefing paper is organised in four parts. We first provide an overview of some general trends in treaty design. In sections 2 to 4, we then take a closer look at selected types of provisions that prove particularly relevant due to their prevalence: (a) general commitments to cooperate on environmental issues; (b) clauses creating international environmental institutions; (c) provisions on technical and financial assistance from one party to another. We find that both the implementation of these provisions and their contribution to environmental protection vary depending on the degree of legal precision, the budgeting of financial resources and governments' political commitment. Based on these findings, we suggest that trade negotiators should i) lay out precise clauses with specific targets and clear time frames, (ii) specify in the trade agreement where the funding for cooperation activities will be sourced and (iii) create forums where civil society actors can engage in a dialogue with policy-makers on the implementation of trade agreements.
Keywords: 330; Handel und Investitionen; Umwelt; Ökosysteme und Ressourcen